Transference Numbers of Vanadium Cations in Nafion. Issue 2 (24th January 2020) - Darling, Robert M.; Saraidaridis, James D.; Shovlin, Christopher; Fortin, Michael
Abstract : Transference numbers for the four vanadium cations present in flow batteries were measured and compared to values derived from permeability and conductivity measurements. The agreement between measured and predicted transference numbers is good. The transference numbers range from ∼0.02 for V(II) and V(III) to ∼0.002 for V(IV) and V(V) at technically relevant vanadium and acid concentrations. The level of agreement between measured and predicted transference numbers suggests that the dilute-solution framework provides a reasonably accurate representation of transport in ion-exchange membranes in vanadium flow batteries.